2011
DOI: 10.1111/j.1440-1789.2011.01203.x
|View full text |Cite
|
Sign up to set email alerts
|

An autopsy case of lymphomatosis cerebri showing pathological changes of intravascular large B-cell lymphoma in visceral organs

Abstract: We describe the case of a 61-year-old man presenting with subacute encephalopathy. The clinical manifestations included progressive dementia and pyramidal and extrapyramidal tract signs. Brain CT scan and MRI showed diffuse bilateral white matter changes in the cerebral hemispheres, basal ganglia, thalamus and brainstem. No contrast-enhanced lesion was observed. Peripheral blood studies, CSF analysis, and brain and muscle biopsies were nonspecific and failed to reveal diagnostic evidence of any specific diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…PCNSL often occurs in the setting of immunosuppression, such as organ transplantation or HIV/AIDS, the latter associated with Epstein-Barr virus infection 10. However, most reported cases of LC have occurred in immunocompetent individuals 11 12…”
Section: Discussionmentioning
confidence: 99%
“…PCNSL often occurs in the setting of immunosuppression, such as organ transplantation or HIV/AIDS, the latter associated with Epstein-Barr virus infection 10. However, most reported cases of LC have occurred in immunocompetent individuals 11 12…”
Section: Discussionmentioning
confidence: 99%
“…The final diagnosis was made following immunostaining for GFAP and other leukocyte markers. CD20 immunostaining allowed us to visualize the extent of infiltration of the lymphoma cells throughout the white matter (11,12). Hans et al subclassified diffuse large B-cell lymphoma into germinal center B-cell-like (GCB) and non-GCB profiles with immunostaining for CD10, bcl-6 and MUM1.…”
Section: Discussionmentioning
confidence: 99%
“…The patient was successfully treated with chemotherapy following the histological diagnosis of hepatic IVL (13). However, due to the difficulty in confirming the suspicion of liver invasion using imaging studies and biopsy methods, to date the number of cases involving the liver diagnosed in the antemortem period is lower than that observed in the postmortem period (12)(13)(14)(15)(16)(17)(18)(19)(20)(21) (Table). Our literature review of hepatic IVL cases diagnosed using imaging studies of the liver revealed that six of 10 cases were diagnosed at autopsy, and no specific findings were observed in the conventional CT studies (Table).…”
Section: Discussionmentioning
confidence: 99%